Study of the 176Hf(n,2n)175Hf cross section at 18.9 MeV - Tsivouraki, Eleni; Chasapoglou, Sotirios; Serris, Michalis; Axiotis, Michael; Gkatis, Georgios; Harissopulos, Sotirios; Kokkoris, Michael; Lagoyannis, Anastasios; Patas, Stavros; Vlastou, Rosa (HNPS Advances in Nuclear Physics, 2022)
Neutron nuclear reactions can provide significant information in the field of nuclear physics and applications. Hafnium (Hf) is one of the rare-earth isotopes with a relative large neutron total cross-section in the thermal neutron energy region and neutron induced reactions in reactor materials could lead to the production of long-lived isomeric states of Hf isotopes. Thus, the knowledge of neutron cross-sections on Hf isotopes is of great importance for basic research in Nuclear Physics as well as for applications concerning the interaction of neutrons with matter. In this study measurements of experimental cross section for the 176Hf(n,2n)175Hf and 180Hf(n,n΄γ)180mHf reactions were carried out, using the activation technique. The neutron beam energy at 18.9 MeV was produced via the 3H(d,n)4He reaction at the 5.5 MeV Tandem Van de Graaf accelerator laboratory of NCSR “Demokritos”. A thin metallic foil of natural Hf was used, while for the determination of the neutron flux at the target position a reference foil of Al was placed at the back of the Hf target. The irradiation was continuous for 28 hours leading to a total neutron fluence of 1010 n/cm2 and a BF3 detector was used for monitoring the neutron flux during the irradiation. After the end of irradiation, the activity of the Hf target and the Al foil were measured off-line by two HPGe detectors. Both detector efficiencies were obtained using a calibrated 152Eu source, placed in the same distance as the target and the reference foil. The 176Hf(n,2n)175Hf reaction has been corrected from the contribution of 177Hf(n,3n)175Hf and the 174Hf(n,γ)175Hf reactions and the 180Hf(n,n΄γ)180mHf reaction from the 179Hf(n,γ)180mHf. Theoretical calculations of the 174Hf(n,2n)175Hf, 176Hf(n,2n)175Hf and 180Hf(n,n΄γ)180mHf reaction cross-sections have also been performed using the nuclear statistical code “EMPIRE 3.2.3” and they have been compared with the data.